TECHNOLOGICAL AND ECONOMIC ASPECTS OF USE OF HYDRATE INHIBITOR FOR GASINDUSTRIAL PROTECTION EQUIPMENT (Oil and Gas Engineering, 2017)
The article analyzes the problems of hydrate formation, which arise in the process of extraction, preparation and transport of gas. The possibility of using a new reagent «RENA-Crystal», as an additive to methanol to prevent hydrate formation in the gas condensate fields. The results of the calculation antigidratnyh properties of «RENA-Crystal». According to the results of industrial tests demonstrated the effectiveness of using a new inhibitor for the prevention of hydrate formation in the training system to Yablunivska comprehensive gas treatment unit. industrial test results confirmed the effectiveness of the «RENA-Crystal» to prevent the formation of hydrates. Keywords: hydrate inhibitor, methanol, gasindustrial equipment, efficiency of use.